Bessel–Gauss Beam Launchers for Wireless Power Transfer - Srdan Pakovic; Siyi Zhou; David Gonzalez-Ovejero; Santi Concetto Pavone; Anthony Grbic; Mauro Ettorre (IEEE Open Journal of Antennas and Propagation, 2021)
In this work, we study the use of Bessel–Gauss beam launchers for wireless power transfer (WPT) applications. The power transfer efficiency between two radiating apertures is investigated in the radiative near field. A spectral Green’s function approach is used to derive the power efficiency under a simultaneous conjugate impedance match. The transverse electromagnetic (TEM) mode of a coaxial cable, as well as Bessel beam (BB) and Bessel–Gauss beam (BGB) field distributions, are considered as aperture distributions. Numerical results demonstrate that a BGB field distribution is the optimal choice for WPT due to its limited spectrum and reduced diffraction of the radiated beam. We synthesized a Bessel–Gauss launcher that exhibits power efficiency exceeding 50% for distances larger than $30λ $ . These results show that non-diffracting beams can pave the way toward efficient near-field WPT systems with extended operating ranges.